In-hospital and one-year outcomes in spontaneous coronary artery dissection. Insights from the Spanish registry on SCAD (SR-SCAD). (14th October 2021) - Garcia Guimaraes, M; Diez-Villanueva, P; Macaya Ten, F; Masotti, M; Sanz-Ruiz, R; Roura, G; Nogales, J M; Abdul-Jawad Altisent, O; Flores-Rios, X; Jimenez-Kockar, M; Veiga, G; Camacho-Freire, S J; et al.
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is a relatively infrequent but well-known cause of acute coronary syndrome (ACS). Information about in-hospital evolution and adverse event during follow-up is still scarce and comes mostly from cohorts outside the European context. Purpose: The aim of the present work was to evaluate in-hospital and one-year follow-up adverse events in a nationwide large prospective cohort of patients with SCAD. Methods: The Spanish Registry on SCAD (NCT03607981) prospectively included patients with a diagnosis of SCAD from 34 Spanish university hospitals. All coronary angiograms were carefully reviewed by two experts at a corelab to confirm the diagnosis of SCAD. In-hospital major adverse event (MAE) was defined as a composite of death, cardiogenic shock, myocardial re-infarction (MI), unplanned revascularization, ventricular arrhythmias (ventricular tachycardia or ventricular fibrillation) or stroke. A predefined 12-month major cardiovascular adverse event (MACE) was defined as a composite of death, MI, unplanned revascularization, SCAD recurrence or stroke. Results: From June 2015 to December 2020, a total of 388 patients (440 lesions) with SCAD were included in the present analysis. Most patients were women (89%), with median age of 53 years old (IQR 47–60). Systemic hypertension (36%), hyperlipidemia (33%) and history of smoking habit (44%) were frequently seen in our cohort. Fifty-six percent of the patients included were postmenopausal. Peripartum context was rare (1.3%). Most patients presented as non-ST-segment-elevation myocardial infarction (NSTEMI) (55%) followed by ST-segment-elevation myocardial infarction (41%). Only 3% of the cohort presented as sudden cardiac death. Left anterior descending coronary artery was most frequently affected (44%), with SCAD lesions predominantly affecting distal (38%) segments and secondary branches (55%). Multivessel involvement was present in 11% of the patients. A long intramural hematoma (type 2 lesion) was the most frequent angiographic pattern (62%). In a vast majority of patients, an initial conservative management was selected (78%). Only in 22% of the SCAD patients the initial strategy was percutaneous coronary intervention. Twenty-four patients (6.2%) had an MAE during admission. The composite was mainly driven by unplanned revascularizations (4.4%) and reinfarctions (2.8%). Only 6 patients (1.6%) died during index admission. At 12-months, 37 patients (10.8%) presented MACE, mainly driven by reinfarctions (5.8%) and unplanned revascularizations (5.8%). Only 1 patient presented SCAD recurrence during 12-month follow-up and 8 patients (2.3%) died. Conclusion: In a large prospective cohort of patients with SCAD, in-hospital and 12 months follow-up prognosis were good. Survival was excellent. A large proportion of the adverse events occurred during the index admission, mainly related to reinfarction and need for revascularization. FUNDunding Acknowledgement: Type of funding sources: None.